Conserving Suklaphanta Wildlife for Sustainable Local Development in Buffer Zone Area - Singh Thakuri, Bir Bahadur (AMC Journal (Dhangadhi), 2026)
This research evaluates the potential for buffer zone activities to contribute to sustainable local development and biodiversity conservation in the Suklaphanta Wildlife Reserve (Nepal). Data were collected from 287 randomly sampled households using mixed-methods. The findings show that buffer zone activities have significantly increased the involvement of the local community in conservation activities, involving 85.4 percent of participants to raise conservation aware, and 65.9 percent to help improve eviction of these HER in community forests. This community involvement has manifested itself in ecological and socio-economic outcomes, with most households (70%) reporting improved populations of wildlife and 65 percent of households reported improved conditions of the forest. Economically, a majority of households (62.1%) reported increased income, and were able to build in asset construction for children’s education (55% of households), livestock (45%), and healthcare access (40%). On the other hand, challenges remain, particularly the challenges of severe human-wildlife conflict (e.g. crop raiding) to 85 percent of households; governance issues, such as delays (60%) in fund disbursement; and (70%) using inadequate alternative livelihoods. The study concludes that while the buffer zone model enables conservation and local development, the long-term sustainability of the initiative rests on effectively managing human-wildlife conflict via mitigation and compensation, improving than transparency and governance and diversifying the local economies/alternative livelihoods through eco-tourism and sustainable forest product use.